The Use of Tea leaves Wastes to reduce Hexavalent Chromium Concentration in industrial Waste Water by Adsorption (Baghdad Science Journal, 2025)
Abstract : A research was conducted to study the process parameters affecting hexavalent chromium Cr (VI) (carcinogenic compound) the removal percentage from the electrical industries company waste water that contain 88 mg/l of Cr (VI) concentration by adsorption onto tea wastes. Synthetic water with 88 mg/l Cr (VI) concentration was used. Several operation parameters affecting Cr (VI) removal efficiency were investigated, such as pH, initial Cr (VI) concentration, stirring time and tea wastes dose. The experimental results reveal that maximum Cr (VI) removal reached up to 94.26% at pH of 2, stirring time of 180 minute, tea wastes dose of 8gm/100 ml and the equilibrium was attained at 180 minute. Langmuir and Freundlich adsorption isotherm models were analyzed and the experimental results fit very well with Freundlich model.